Factors influence the effectiveness of Malaysia Credit Counselling and Debt Management Agency (CCDMA) programme / Jeffery Bueh and Norziana Lokman - Bueh, Jeffery; Lokman, Norziana (Universiti Teknologi MARA, Shah Alam, 2017)
The effectiveness of Credit Counselling and Debt Management Agency (CCDMA) programme has become commonly important today due to the increase in the bankruptcy cases in Malaysia especially in Selangor state. As Malaysia move towards becoming developed country, the rise of bankruptcy cases have become the threat to the economic development of the country. Bankruptcy cases in Malaysia happen due to the uncontrollable household lending activities. Although as much as the economic is concern, household lending activities can promote the economic development but at certain point, the household lending activities could become a problem to the economic development of the country. Therefore, this study aims to examine the factors that influence the effectiveness of the CCDMA in Selangor, Malaysia. This study used quantitative approach via questionnaire survey to collect the data. Promotional activities, programme contents, public attitudes and stigma are the preditors to the effectiveness of CCDMA programme. The finding of this study reveals that promotional activities, public attitudes and programme contents play a very significant role in ensuring the effectiveness of CCDMA programme. The finding provide empirical evidence that CCDMA may improve it roles in helping young working adults dealing with household indebtness and indirectly help government to improve economy of the country.